2010
DOI: 10.1051/meca/2010039
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical contact analysis on the interfaces in a proton exchange membrane fuel cell

Abstract: The power density of a proton exchange membrane fuel cell (PEMFC) depends on several parameters. The contact resistance between the bipolar plate (BPP) and the gas diffusion layer (GDL) and the porosity of the GDL are two main parameters involved in the performance of the PEMFC. The purpose of this work is to develop a numerical model to describe the contact behavior (contact zone, contact force) on the interfaces between the different layers in order to propose an optimal structure for the high performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The end plates are one of the main components located opposite of the fuel cell stack as shown in Figure 1, which can fasten the BPPs, MEAs, sealants and current collection plates together with enough clamping force in order to evite •3• the leakage of the hydrogen, and meanwhile provide a uniform contact pressure between components of the fuel cell stack. The contact pressure on the multiple contact interfaces plays a key role to affect the mechanical strength of MEA and also the contact behavior between BPP and MEA, consequently the failure or critical damage of MEA [7][8][9], gas transportation [10][11][12] and the electric resistance [13][14][15], eventually the performance and durability of the fuel cell stack.…”
Section: Figure 1 Schematic Of Components Of the Fuel Cell Stackmentioning
confidence: 99%
“…The end plates are one of the main components located opposite of the fuel cell stack as shown in Figure 1, which can fasten the BPPs, MEAs, sealants and current collection plates together with enough clamping force in order to evite •3• the leakage of the hydrogen, and meanwhile provide a uniform contact pressure between components of the fuel cell stack. The contact pressure on the multiple contact interfaces plays a key role to affect the mechanical strength of MEA and also the contact behavior between BPP and MEA, consequently the failure or critical damage of MEA [7][8][9], gas transportation [10][11][12] and the electric resistance [13][14][15], eventually the performance and durability of the fuel cell stack.…”
Section: Figure 1 Schematic Of Components Of the Fuel Cell Stackmentioning
confidence: 99%
“…The least thickness of the endplate can be obtained by this pre-curvature design. Carral et al 19,20 developed a FEA model to investigate the effect of the different numbers of cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and their position on the endplates of the fuel cell stacks, the results revealed that with the greatest number of cells, a better uniformity of the contact pressure on MEA could be obtained. The deflection of endplates can be indicated the uniformity of contact pressure on the MEA.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical properties of the GDL and membrane are sharply changed, which lead to eventual failure of their physical properties. Indeed, the variation of internal stresses and contact pressure between the assembly elements of a PEMFC fuel cell causes larges stains 2 . This result is produced by the changes in its mechanical, electrochemical and thermal characteristics.…”
Section: Introductionmentioning
confidence: 99%